2015
DOI: 10.5194/isprsarchives-xl-1-w5-625-2015
|View full text |Cite
|
Sign up to set email alerts
|

3d Building Façade Reconstruction Using Handheld Laser Scanning Data

Abstract: ABSTRACT:3D The three dimensional building modelling has been an interesting topic of research for decades and it seems that photogrammetry methods provide the only economic means to acquire truly 3D city data. According to the enormous developments of 3D building reconstruction with several applications such as navigation system, location based services and urban planning, the need to consider the semantic features (such as windows and doors) becomes more essential than ever, and therefore, a 3D model of buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Müller et al [6] suggested an image-based façade reconstruction approach method by utilizing an image analysis algorithm to divide the façade into meaningful segments and combine the procedural modeling pipeline of shape grammars to ensure the regularity of the final reconstructed model. Sadeghi et al [7] presented an approach for façade reconstruction from hand-held laser scanner data based on grammar. The method starts from using RANSAC method to extract façade points, and then protrusion, indentation, and wall points are detected by utilizing a density histogram.…”
Section: Introductionmentioning
confidence: 99%
“…Müller et al [6] suggested an image-based façade reconstruction approach method by utilizing an image analysis algorithm to divide the façade into meaningful segments and combine the procedural modeling pipeline of shape grammars to ensure the regularity of the final reconstructed model. Sadeghi et al [7] presented an approach for façade reconstruction from hand-held laser scanner data based on grammar. The method starts from using RANSAC method to extract façade points, and then protrusion, indentation, and wall points are detected by utilizing a density histogram.…”
Section: Introductionmentioning
confidence: 99%
“…The naive approach to keeping the model updated is to perform a regular and comprehensive 3D scan of the environment. However, even with an efficient processing of the acquired data, data collection remains time consuming, expensive [7][8][9][10][11], and requires appropriate equipment [12][13][14]. To solve this issue, many techniques have been developed to accurately locate the 3D locations of changes in an environment based on the comparison of an offline and thus outdated 3D mesh of the scene and a sequence of current images.…”
Section: Introductionmentioning
confidence: 99%